Reaktualisasi Reformasi Birokrasi Melalui Pemangkasan Birokrasi (Studi Kasus: BKPSDM Provinsi Bali): Reactualization of Bureaucratic Reform Through Bureaucratic Reduction (Case Study: BKPSDM of Bali Province) - Wahyuni, Desak Ayu Candra; Subanda, I Nyoman (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
This study aims to determine the process of re-realization of bureaucratic reform through the implementation of bureaucratic simplification in the BKPSDM of Bali Province and the obstacles faced in realizing bureaucratic reform in the implementation of bureaucratic simplification. This study uses a qualitative descriptive research method. The results of the study indicate that the process of reactualization of bureaucratic reform has gone well by referring to regulations that are oriented towards results and are applicable, the implementation process is measurable, synergistic, so that innovation of the apparatus and its implementation are monitored. In fact, several aspects such as the efficiency of resource use, the effectiveness of adaptation of new work systems, the realism of hierarchy reduction and the consistency of preparing individual employee skills and expertise have not been implemented optimally. The obstacles faced are the lack of competency development for functional position holders due to equalization, bureaucratic simplification regulations that still need to be reviewed and evaluated, there are still functional position holders with old work pattern mindsets, and limited implementation time targets. Implications for further research can use more complete aspects of bureaucratic simplification and can conduct research in several other Regional Devices (PD) in order to get more comprehensive results.